HIV/AIDS in South Africa: how many people died from the disease between 1997 and 2010?. (13th March 2016) - Bradshaw, Debbie; Msemburi, William; Dorrington, Rob; Pillay-van Wyk, Victoria; Laubscher, Ria; Groenewald, Pam
Abstract : Objectives: Empirical estimates of the number of HIV/AIDS deaths are important for planning, budgeting, and calibrating models. However, there is an extensive misattribution of HIV/AIDS as an underlying cause-of-death. This study estimates the true numbers of AIDS deaths from South African vital statistics between 1997 and 2010. Methods: Individual-level cause-of-death data were grouped according to a local burden of disease list and source causes (i.e. causes under which AIDS deaths are misclassified) that recorded a rapid increase. After adjusting for completeness of registration, the mortality rate of the source causes, by age and sex, was regressed on the lagged HIV prevalence to estimate the rate of increase correlated with HIV. Background trends in the source-cause mortality rates were estimated from the trend experienced among 75–84 year olds. Results: Of 214 causes considered, 19 were identified as potential sources for cause misattribution. High proportions of deaths from tuberculosis, lower respiratory infections (mostly pneumonia), diarrhoeal diseases, and ill-defined natural causes were estimated to be HIV-related, with only 7% of the estimated AIDS deaths being recorded as HIV. Estimated HIV/AIDS deaths increased rapidly, then reversed after 2006, totalling 2.8 million deaths over the whole period. The number was lower than model estimates from Joint United Nations Programme on HIV/AIDS (UNAIDS) and the Global Burden of Disease Study. Conclusion: Empirically based estimates confirm the considerable loss of life from HIV/AIDS and should be used for calibrating models of the AIDS epidemic which generally appear too low for infants but too high for other ages. Doctors are urged to specify HIV on death notifications to provide reliable cause-of-death statistics. Abstract : Supplemental Digital Content is available in the text